Dielectric Relaxation Processes, Electronic Structure, and Band Gap Engineering of MFU‐4‐type Metal‐Organic Frameworks: Towards a Rational Design of Semiconducting Microporous Materials. (18th March 2014) - Sippel, Pit; Denysenko, Dmytro; Loidl, Alois; Lunkenheimer, Peter; Sastre, German; Volkmer, Dirk
<x xml:space="preserve">Abstract</x> The electronic structures and band gaps of MFU‐4‐type metal‐organic frameworks can be systematically engineered leading to a family of isostructural microporous solids. Electrical properties of the microcrystalline samples are investigated by temperature‐dependent broad‐band dielectric and optical spectroscopy, which are corroborated by full band structure calculations performed for framework and cluster model compounds at multiple levels of density functional theory. The combined results glean a detailed picture of relative shifts and dispersion of molecular orbitals when going from zero‐dimensional clusters to three‐dimensional periodic solids, thus allowing to develop guidelines for tailoring the electronic properties of this class of semiconducting microporous solids via a versatile building block approach. Thus, engineering of the band gap in MFU‐4 type compounds can be achieved by adjusting the degree of conjugation of the organic ligand or by choosing an appropriate metal whose partially occupied d‐orbitals generate bands below the LUMO energy of the ligand which, for example, is accomplished by octahedral Co(II) ions in Co‐MFU‐4.